Malaysian fisheries policy beyond 2000 - Mohd Mazlan Jusoh (Universiti Putra Malaysia, 2015)
There are many new issues, conflicts and challenges that the fisheries sector will encounter with the turn of the century. Faced with increasing pressure from coastal land development, environmental deterioration and over exploitation of natural resources to meet ever increasing demands, it is inevitable that management of the fisheries sector will be a challenging task. Malaysia has invested and will continue to invest both manpower and finance into developing and managing the fishery resources in order to increase production through the rational exploitation of the natural resources and also by various forms of aquaculture. The fisheries policy adopted by Malaysia is targeted towards the exploration and exploitation of resources in new areas in the offshore waters and in aquaculture on a large-scale commercial basis. At the same time, Malaysia will continue to give great importance to the maintenance of the existing coastal fisheries which are expected to contribute the bulk of marine fish landings and provide employment to a major propotion of the fishing labour force. The objective of the policy is the development of the fishing industry, be it capture fisheries or aquaculture, on a modern, commercialised basis involving the corporate sector and entrepreneurs. While maximising the exploitation, the Government is committed to ensuring that the resources are sustainable in the long term and that aquaculture does not degrade the environment or cause a deterioration in the water quality of the coastal area. The Government, under the Malaysia Incorporated Concept, will ensure a better relationship between the Government and private sector. This will lead to a greater dynamism and aggressiveness in the development of the industry. While the Government can set up policies and regulations and provide infrastructure and incentives, ultimately it is the private sector that needs to play the main role in achieving the country`s growth.